PREVALENCE OF ULCERATIVE DERMATITIS IN OLIVE RIDLEY HATCHLINGS REARED AT TURTLE CONSERVATION AND EDUCATION CENTRE SERANGAN - Wijaya, Annabella Ruth; Adnyana, Ida Bagus Windia; Kardena, I Made (Buletin Veteriner Udayana, 2018)
Ulcerative dermatitis is a disease that most commonly affects turtles and/or hatchlings that are kept in ponds, including in Turtle Conservation and Education Center (TCEC), Serangan. A study was conducted to determine the prevalence, pathology, and lesion location of ulcerative dermatitis in olive ridley hatchlings reared in TCEC Serangan, also the differences of the body condition index of olive ridley hatchlings with ulcerative dermatitis and healthy ones. Prevalence was determined by counting sick hatchlings compared with the total number of hatchlings at TCEC. Morphometry ( s traight carapace length, straight carapace width, curved carapace length, curved carapace width) and body weights were measured to determine the body condition index, and then body index differences were compared with unpaired T-Test. Skin tissue samples were processed into pathology slides and routinely staining of hematoxylin eosin (HE). The prevalence of ulcerative dermatitis in olive ridley hatchlings at TCEC was 16.2%. Crusty-yellow wound lesions of 2 mm to 2 cm in diameter were found and microscopically there were heterophils and mononuclear cells infiltration in skin dermis accompanied by erosion, parakeratosis, and necrotic material containing cell debris. Lesions were found mostly on neck area (63.04%), followed by flippers, head, skin near carapace, eyelids, and neck area with flippers combined. There was a very significant difference in body condition index between suffered hatchlings with healthy ones, where the average body condition index of suffered hatchlings were greater than healthy ones. Rearing management should be fixed.